Why Punjab needs incentives, not loan waivers - Joshi, Pramod Kumar; Khan, Md. Tajuddin; Kishore, Avinash (2017)
Punjab farmers would benefit if the state govt subsidised the adoption of appropriate technology and diversification of crops.